Intelligent information processing IX : 10th IFIP TC 12 International Conference, IIP 2018, Nanning, China, October 19-22, 2018, Proceedings /: 10th IFIP TC 12 International Conference, IIP 2018, Nanning, China, October 19-22, 2018, Proceedings. (2018) - Unknown
No abstract available